Effect of Denosumab on Bone Mineral Density of Hematopoietic Stem Cell Transplantation Recipients - Chaiho Jeong; Hee-Je Kim; Seok Lee; Moo Il Kang; Jeonghoon Ha (International Journal of Endocrinology)
Purpose. Denosumab is a monoclonal antibody that prevents the development of osteoclasts. The effect of denosumab in solid organ transplant recipients has been elucidated, but its effect in haematopoietic stem cell transplantation recipients has not been studied yet. The aim of this study was to determine the effectiveness and safety of denosumab in haematopoietic stem cell transplantation recipients. Methods. We retrospectively evaluated 33 female patients with osteoporosis (mean age 52.6 ± 9.8 years) following allogeneic haematopoietic stem cell transplantation. Patients were treated with denosumab every 6 months for 12 months. Changes in bone mineral density were evaluated for denosumab-treated patients in a 12-month interval after the first administration of denosumab. Results. Significant increases in bone mineral density were observed in all measured skeletal sites including 4.39 ± 6.63% in the lumbar spine (p=0.014), 3.11 ± 7.69% in the femoral neck (p=0.048), and 1.97 ± 6.01% in the total hip (p=0.138). The bone turnover marker serum cross-linked C-terminal telopeptide of type 1 collagen was decreased at 18 months (−51.6 ± 17.6%, p<0.001). No serious symptomatic hypocalcaemia was observed. Serious adverse drug reactions requiring drug discontinuation were not observed. Conclusion. Denosumab improved bone mineral density in haematopoietic stem cell transplantation recipients. The use of denosumab could be a good therapeutic option without causing severe adverse effects in recipients of haematopoietic transplantation.